Economics of aquaculture feeding practices in selected Asian countries (Food and Agriculture Organization of the United Nations, 2007)
It comprise s of six selected country case study reports from Asia (Bangladesh, China, India, the Philippines, Thailand and Viet Nam) and an overall synthesis ending with conclusions and recommendations.